A study on multi-agent systems for stable matching - Mohd Syakirin, Ramli (2015)
The studies in the multi-agents system (MAS) have attracted many researchers from various fields. The focal point of investigation in MAS has not only surrounded on the development of the control algorithms, but nowadays covers on the practically to use MAS as one of the problem solvers in the other fields of studies.